Crinoids of the stalked family Hyocrinidae (Echinodermata) collected by the USNS Eltanin in the Southern Ocean - Roux, Michel (Zootaxa, 2015)
Rare species only known from one or a few specimens, mainly collected from abyssal and hadal zones in the Southern Ocean are represented in a collection of stalked crinoids attributed to the family Hyocrinidae (Crinoidea, Echinodermata). The species studied here include Belyaevicrinus latipinnulus Mironov & Sorokina, 1998, Feracrinus heinzelleri Bohn, 2012, Ptilocrinus brucei Vaney, 1908 and Thalassocrinus clausus Mironov & Sorokina, 1998. This collection, mainly collected during the 1960s USNS Eltanin cruises, is housed at the Smithsonian Institution National Museum of Natural History in Washington DC. A detailed study of this material using SEM observations of ossicle articular facets and pinnule architecture allows the emendation of species diagnoses, and a better description of intraspecific variation and of changes in characters through ontogeny. Geographical and depth range extension of species are reported. A gonad with submature ovocytes of 100–150 µm was exceptionally preserved at the base of a genital pinnule of P. brucei. This species likely has a lecithotrophic larval development.